An Analysis Of Students' Ability In Writing Generic Structure Of Recount Text - Novita Yulianti; Yessy Marzona; Lailatul Husna (Kilau Publishing, 2025)
In English lessons, writing ability is one of the challenges for students. Analyzing students' abilities is the key to developing effective methods, especially in writing recount texts based on their generic structure. Therefore, the purpose of this study is to analyze students' abilities in writing recount texts based on their generic structure. This study uses a descriptive method with a quantitative design. In this study, the researcher also used cluster random sampling in two classes, namely class X DPIB 1 and DPIB 2. Then the researcher chose one of the two classes, namely class X DPIB 1, which consisted of 25 students. Data were collected through a writing test. In conclusion, the results of the study showed that most students had moderate writing abilities, with a score of 56% in the writing component. Although they performed well in the orientation section, they struggled in the event section, lacking details and proper sequence. Overall, their ability in writing recount texts based on generic structure was classified as good, with a score of 3.28.